The Link Between Adherence to International Standards of Good Practice, Foreign Exchange Spreads, and Ratings - Tiffin, Andrew (IMF Working Papers; Working Paper, 2003)
This paper examines the relationship between adherence to international standards of good practice in policy-making and two key indicators of access to capital markets and the cost of this access: spreads and sovereign ratings. In contrast to other work, this study reviews a broad set of indicators for adherence to international standards. The estimations are conducted for emerging market economies, and pay particular attention to issues of persistence in spreads and ratings and nonlinearities in the relationships. The main finding confirms the expectation that standards are indeed relevant. Accounting standards and property rights are especially important for spreads, in addition to data transparency (SDDS subscription). Accounting standards and corruption are especially important in explaining ratings in addition to trade protectiveness (not a standard).